Pharmacological effects of methylone and MDMA in humans - Poyatos, Lourdes; Pérez-Mañá, Clara; Hladun, Olga; Núñez-Montero, Melani; de la Rosa, Georgina; Martín, Soraya; Barriocanal, Ana Maria; Carabias, Lydia; Kelmendi, Benjamin; Taoussi, Omayema; Busardò, Francesco Paolo; Fonseca, Francina; et al. (Frontiers in Pharmacology, 2023)
Methylone is one of the most common synthetic cathinones popularized as a substitute for 3,4-methylenedioxymethamphetamine (MDMA, midomafetamine) owing to its similar effects among users. Both psychostimulants exhibit similar chemistry (i.e., methylone is a β-keto analog of MDMA) and mechanisms of action. Currently, the pharmacology of methylone remains scarcely explored in humans. Herein, we aimed to evaluate the acute pharmacological effects of methylone and its abuse potential in humans when compared with that of MDMA following oral administration under controlled conditions. Seventeen participants of both sexes (14 males, 3 females) with a previous history of psychostimulant use completed a randomized, double-blind, placebo-controlled, crossover clinical trial. Participants received a single oral dose of 200 mg of methylone, 100 mg of MDMA, and a placebo. The variables included physiological effects (blood pressure, heart rate, oral temperature, pupil diameter), subjective effects using visual analog scales (VAS), the short form of the Addiction Research Center Inventory (ARCI), the Evaluation of Subjective Effects of Substances with Abuse Potential questionnaire (VESSPA-SSE), and the Sensitivity to Drug Reinforcement Questionnaire (SDRQ), and psychomotor performance (Maddox wing, psychomotor vigilance task). We observed that methylone could significantly increase blood pressure and heart rate and induce pleasurable effects, such as stimulation, euphoria, well-being, enhanced empathy, and altered perception. Methylone exhibited an effect profile similar to MDMA, with a faster overall onset and earlier disappearance of subjective effects. These results suggest that abuse potential of methylone is comparable to that of MDMA in humans.